Effects of water, ammonia and formic acid on HO2 + Cl reactions under atmospheric conditions: competition between a stepwise route and one elementary step. Issue 37 (10th July 2019) - Zhang, Tianlei; Zhang, Yongqi; Wen, Mingjie; Tang, Zhuo; Long, Bo; Yu, Xiaohu; Zhao, Caibin; Wang, Wenliang
Abstract : The effects of acidic (FA), neutral (WM) and basic (AM) catalysts on the energetic and kinetic aspects of the HO2 + Cl reaction have been studied. At 298 K, the catalytic order of FA, WM and AM is WM > FA > AM. Abstract : Quantum chemical calculations at M06-2X and CCSD(T) levels of theory have been performed to investigate the effects of H2 O, NH3, and HCOOH on the HO2 + Cl → HCl + O2 reaction. The results show that catalyzed reactions with three catalysts could proceed through two different mechanisms, namely a stepwise route and one elementary step, where the former reaction is more favorable than the latter. Meanwhile, for the stepwise route, a single hydrogen atom transfer pathway in the presence of all catalysts has more advantages than the respective double hydrogen atom transfer pathway. Then, the relative impacts of catalysts under tropospheric conditions were investigated by considering the temperature dependence of the rate constants and the altitude dependence of catalyst concentrations. The calculated results show that at 0 km altitude, the HO2 + Cl → HCl + O2 reaction with catalysts, such as H2 O, NH3, or HCOOH, cannot compete with the reaction without a catalyst, as the effective rate constant with a catalyst is smaller by 2–6 orders of magnitude than the naked reaction within the temperature range 280–320 K. The calculated results also show that at altitudes of 5, 10 and 15 km, the effective rate constant of the HCOOH-catalyzed reaction increases obviously with an increase in altitude. At 15 km altitude, its value is up to 9.63 × 10 −11 cm 3 per molecule per s, which is close to the corresponding value of the reaction without a catalyst, showing that the contribution of HCOOH to the HO2 + Cl → HCl + O2 reaction cannot be neglected at high altitudes. The new findings in this investigation are not only of great necessity and importance for elucidating the gas-phase reaction of HO2 with Cl in the presence of acidic, neutral and basic catalysts, but are also of great interest for understanding the importance of other types of hydrogen abstraction in the atmosphere.